2009
DOI: 10.1177/147323000903700112
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Characteristics of Human Third Trimester Amniotic Fluid Stem Cells

Abstract: Third trimester amniotic fluid (AF)-derived human mesenchymal stem cells (MSCs) can be greatly expanded in vitro and induced to differentiate into multiple mesenchymal cell types. This study aimed to investigate the biological characteristics of MSCs from third trimester AF as a new source of therapeutic stem cells. Forty third trimester AF samples were obtained from healthy women who underwent elective caesarean section for breech presentation. A simple culture protocol for MSCs was used. A cell growth curve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 14 publications
2
33
1
5
Order By: Relevance
“…During subsequent days of cultivation they proliferate rapidly. Similar observations were recorded by other authors, not only in human but also in other species (Yang et al 2001;Arrigoni et al 2009;You et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…During subsequent days of cultivation they proliferate rapidly. Similar observations were recorded by other authors, not only in human but also in other species (Yang et al 2001;Arrigoni et al 2009;You et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…The cell population with the fusiform appearance described here in samples from both adipose tissue and bone marrow were morphologically similar to mesenchymal stem cells from human (Zuk et al 2001, You et al 2009), sheep (Fadel et al 2011), horse (Fortier et al 1998, Smith et al 2003, Hegewald et al 2004, Vidal et al 2006, 2007, Maia et. al 2012, De Vita et al 2013, and other animals reported in many studies, in which these cells were described as star-shaped or fibroblast-like.…”
Section: Discussionmentioning
confidence: 78%
“…Electron microscopy analysis showed morphology similar to mesenchymal stem cells derived from other tissues (for example described by Danišovič et al 2008;You et al 2009;Arnold et al 2010), but the origin and biological potential of HDPSCs is probably different.…”
Section: Discussionmentioning
confidence: 98%